The Idea of Modern Kitchen in Projects of the Catering Establishments Development in Poland in the 1950s and 1960s - Czekalski, Tadeusz (In the Kitchen. Cultural Sketches on Space, 2019)
The pattern of home kitchen to which the first French restaurants turned out became anachronic in the face of the increase of catering properties in 19th century and the need to prepare meals on a massive scale. Return to systems similar to home kitchen but used in catering was implemented during First World War canteen projects. A similar one was realized in the 1920s in Soviet Union but in this case the development of collective kitchens had to implement the ideological plan of home kitchen degradation. Discrediting homemade food for meals in canteens was to attempt and abandonment of time consuming cook of small portions prepared at home according to traditional recipes. The project of canteens development on massive scale took place in Poland since the beginning of 1950’s. Referring to the Soviet patterns mechanized kitchens, using semi-prepared meals and producing standardized dishes reasonably turned out to be in practice an unfulfilled utopia. Slogans of kitchen modernization in Poland during the first two decades of communist regime should be considered as ideological postulate that greatly remained in the sphere of unrealized project actually suited “higher” meaning the practices of institutionalization – through attempts of rationalization and control of everyday life practices.